2015
DOI: 10.5120/ijca2015905428
|View full text |Cite
|
Sign up to set email alerts
|

Using Mobile Platform to Detect and Alerts Driver Fatigue

Abstract: When driver is in the state of drowsiness he can cause accidents. This state is the state between being awake and asleep. In this state driver reaction time is slower, his attentiveness is reduced, and his information processing is less efficient. Driver Fatigue Detection System (called FDS) has been proposed by the authors in a recent work. The FDS aims to monitor the driver and the alertness to prevent them from falling asleep at the wheel. FDS is very hard to fix in a car. In the present paper, the FDS soft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Some studies have reported the use of external sensors in conjunction with embedded sensors in mobile devices to address traffic issues (8,12,13,15,17,18,22,24,29,(36)(37)(38)(39)(40)(41). Camera sensors, for example, collect data from various sources such as facial and eye expressions, road images, road potholes, and traffic signs (19,21,25,31,(42)(43)(44)(45). Accelerometer and magnetometer sensors receive sudden braking, fast rotation, and fast acceleration data (36,(46)(47)(48).…”
Section: Information Management Aspects Of Mobile Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reported the use of external sensors in conjunction with embedded sensors in mobile devices to address traffic issues (8,12,13,15,17,18,22,24,29,(36)(37)(38)(39)(40)(41). Camera sensors, for example, collect data from various sources such as facial and eye expressions, road images, road potholes, and traffic signs (19,21,25,31,(42)(43)(44)(45). Accelerometer and magnetometer sensors receive sudden braking, fast rotation, and fast acceleration data (36,(46)(47)(48).…”
Section: Information Management Aspects Of Mobile Solutionsmentioning
confidence: 99%
“…-apps to monitor traffic patterns and driving behavior (12-17) -apps to reduce fuel consumption (18) -apps to detect drowsiness (19)(20)(21) -apps to detect car accidents (22)(23)(24) -apps to inform of real-time road conditions (25-27) -apps for safe driving (28)(29)(30)(31)(32) A comprehensive categorization of traffic and road safety applications was carried out in a prior study, employing the Haddon matrix as a framework to discern the features of the applications (33). To the best of our knowledge, a comprehensive review of the academic literature on mobile solutions for traffic and road safety issues has not been conducted.…”
mentioning
confidence: 99%
“…The argument is that increased mileage should not be viewed as risk reducing, since a driver who decides to drive more miles has a fixed claims probability for their original driven distance and the additional distance can only increase that probability, although the marginal increase in probability of claims per mile may decrease with additional miles driven. Some studies have examined drowsiness detection using wearable headbands (Rohit et al 2017), or fatigue using computer vision techniques (Abulkhair et al 2015). There have been studies analyzing driver behavior using information acquired from a vehicle's CAN (controller area network) bus, detailing sequences of actions including braking and turning events, steering wheel angle, and vehicle speed, most often in an attempt to identify drivers based on the information obtained from the CAN bus.…”
Section: Telematics Datamentioning
confidence: 99%
“…The usage of smart phone greatly reduces the complexity of video acquisition, store and transmission [14]- [16]. However, since driver's driving environment is highly dynamic, most of the smart phone based algorithms are very susceptible to the dynamics in driving environment because the mobile platform cannot afford the computation and storage requirement for very sophisticated algorithms.…”
Section: Introductionmentioning
confidence: 99%